Sobre a desintegração de prótons em movimento circular em campos gravitacionais - Fregolente, D [UNESP] (2007)
We investigate the possible decay of protons in geodesic circular motion around neutral compact objects. Weak and strong decay rates and the associated emitted powers are calculated using a semi-classical approach. Our results are discussed with respect to distinct ones in the literature, which consider the decay of accelerated protons in electromagnetic fields. A number of consistency checks are presented along this thesis